Implementasi Sistem Informasi Sumber Daya Manusia dan Manfaatnya bagi Organisasi - Muhamad Dzakir Jibral Raflian (Applied Business and Administration Journal, 2022)
The development and use of information management systems (MIS) is a modern phenomenon concerned with the proper use of information which will lead to better planning, better decision making, and better results. In a company or organization there are various benefits of an information system if we use it properly. The role of a management that demands the deployment and use of annefficient resource to achieve a goal. And so will encourage the management function by receiving more information. quick and precise. So trying to find the effect of the application of Human Resources Information Systems towards time efficiency, cost efficiency, information quality, and managerial satisfaction.